Single vesicle analysis reveals nanoscale membrane curvature selective pore formation in lipid membranes by an antiviral α-helical peptide - Zhdanov, Vladimir P. (2013)
Using tethered sub-100 nm lipid vesicles that mimic enveloped viruses with nanoscale membrane curvature, we have in this work designed a total internal reflection fluorescence microscopy-based single vesicle assay to investigate how an antiviral amphipathic α-helical (AH) peptide interacts with lipid membranes to induce membrane curvature-dependent pore formation and membrane destabilization. Based on a combination of statistics from single vesicle imaging, binding kinetics data, and theoretical analysis, we propose a mechanistic model that is consistent with the experimentally observed peptide association and pore formation kinetics at medically relevant peptide concentrations (10 nM to 1 μM) and unusually low peptide-to-lipid (P/L) ratio (1/1000). Importantly, the preference of the AH peptide to selectively rupture virions with sub-100 nm diameters appears to be related to membrane strain-dependent pore formation rather than to previously observed nanoscale membrane curvature facilitated binding of AH peptides. Compared to other known proteins and peptides, the combination of low effective P/L ratio and high specificity for nm-sized membrane curvature lends this particular AH peptide great potential to serve as a framework for developing a highly specific and potent antiviral agent for prophylactic and therapeutic applications while avoiding toxic side effects against host cell membranes.